LIPID-LOWERING THERAPY IN OUTPATIENT PRACTICE (ACCORDING TO THE ARGO-2 STUDY) - N. M. Akhmedzhanov; D. V. Nebieridze; A. S. Safaryan; V. A. Vygodin; A. Yu. Shuraev; A. N. Tkacheva; A. S. Lishuta (Столичная издательская компания, 2016)
Aim. To study the features of lipid-lowering therapy with rosuvastatin in high and very high cardiovascular risk patients in real outpatient practice.Material and methods. Patients ≥30 years, visited internists or cardiologists of district outpatient clinics in the period from October 2013 to July 2014 were included into the study. Each patient fill in questionnaire. Determination of total cholesterol (TC) level was performed without special preparation of the patient using a portable photometric blood analyzer. Doctors prescribed rosuvastatin therapy when indicated, in accordance with the Guidelines, choosing the dose on their own. Repeated TC level was determined after 1 month.Results. TC level was initially determined in 10547 patients. Rosuvastatin treatment was recommended for all patients. Repeated TC level determination was performed in 7897 patients in an average after 33 days. Baseline TC level in them was 6.37±0.89 mmol/l, and after 1 month while taking rosuvastatin - 4.89±0.81 mmol/l (p<0.001). The change of TC level was -22% (p<0.001). The average prescribed dose of rosuvastatin was 11.88±5.1 mg per day. The most often (62.8%) rosuvastatin was prescribed in a dose of 10 mg per day, in 27.3% of patients - 20 mg per day, in 9.2% - 5 mg per day, and only 0.5% of patients took it in the maximal dose.Conclusion. In real clinical practice, rosuvastatin for treatment of patients with high or very high cardiovascular risk is often prescribed in moderate doses and rarely in the maximum dose despite the proven lipid-lowering effect.